Diagnosis Kebuntingan Kuda Menggunakan Kit mare Test Pack - Ali Saifudin; Siti Aslimah; Lia Nur Aini; Theo Mahiseta Syahniar (Politeknik Negeri Jember, 2019)
This research aimed to diagnosed pregnancy on mares using a test mare (MTP) kit. This study using 10 mares were used to confirm their pregnancy status using a rectal exploration technique (gold standard) using seven pregnant mares (K1) and three non-pregnant mares (K2). Serums from both groups were tested using a MTP kit. The research data were tested descriptive. The results showed that seven mares that were positively pregnant and three negative mares unpregnant after being tested using the MTP kit and rectal exploration. The conclusion that the MTP kit can be used to diagnose pregnancy in mares of 60 to 100 pregnancy days which is 100% accuracy sensitivity and specificity.Â